Система соціального захисту населення України та її проблеми - Агєєва, Ірина Вікторівна; Ahieieva, Iryna (Мелітополь : ТДАТУ, 2022)
UA: В статті визначено теоретичні, організаційно-економічні та науково-практичні аспекти соціального захисту населення в Україні їх проблеми та шляхи вирішення. Визначено пріоритетні напрямки, проблеми та розвиток соціальної сфери України на шляху до євроінтеграції. Проаналізовано умови функціонування діючої системи соціального захисту населення України. Визначено, що становлення соціального захисту та збільшення впливу соціального захисту на добробут населення прописано в Конституції України, а розвиток інших соціальних складових має належним чином регулюватися державою. EN: The article identifies theoretical, organizational, economic and scientific and practical aspects of social protection in Ukraine, their problems and solutions. The priority directions, problems and development of the social sphere of Ukraine on the way to European integration are determined. The conditions of functioning of the current system of social protection of the population of Ukraine are analyzed. It is proved that the problem of proper social protection of low-income and privileged categories of citizens through the introduction of state social benefits aims to create conditions under which such citizens will be able to legal and material support to overcome a difficult situation that may be a manifestation of social risk in general. It is determined that the formation of social protection and increase its impact on the welfare of the population is enshrined in the Constitution of Ukraine, and the development of other social components should be properly regulated by the state.
System of social protection of the population of Ukraine and its problems
Keywords: населення; соціальний захист; розвиток; проблеми; матеріальне забезпечення; соціальне страхування; матеріальна допомога; population; social protection; development; problems; material security; social insurance; material assistance